IMPLEMENTASI POTONGAN DAGING DI BUTCHER SECTION - Dedi Mulyadi; Dendi Gusnadi (Media Bina Ilmiah, 2024)
This paper examines the implementation of butchery techniques in the butcher section, with a focus on the effectiveness of cutting methods in determining meat quality and its impact on operational efficiency and food safety. Correct cutting techniques play a key role in producing high-quality cuts, minimizing waste, and ensuring food safety. This study explores various cutting techniques for beef, poultry, and seafood, and their impact on meat taste, texture, and tenderness. In addition, the paper highlights the importance of using modern technology and ongoing training to improve meat cut quality and operational efficiency. The results show that the adoption of correct cutting techniques, appropriate tools, and strict sanitation practices can significantly improve the final meat yield and consumer satisfaction. The paper also provides recommendations for further research in the areas of cutting technology, staff training, and waste management to support the development of best practices in the butchery industry.